Artificial diet for laboratory rearing of Condylorrhiza vestigialis (Guenée, 1854) (Lep.: Crambidae) - CAMPOS,LUCAS S. (2017)
ABSTRACT The Brazilian Poplar Moth, Condylorrhiza vestigialis (Guenée), compromises the wood productivity of poplar trees (Populus sp.), mainly affecting the matchstick industry in southern Brazil. Considering the lack of information on rearing techniques for this insect, the objective of this study was to develop an artificial diet to rear C. vestigialis with biological characteristics similar to the wild insects. A properly diet will enable bio-ecological studies and biological control programs using the baculovirus Condylorrhiza vestigialis multiple nucleopolyhedrovirus (CvMNPV). To attain this objective, first, three artificial diets were tested. Only the diet based on corn, wheat germ and yeast as a protein source (Diet 3) was able to supply the nutritional requirements of the moth and support completion of its life cycle. In the second experiment, Diet 3 was compared to the natural diet of C. vestigialis. The artificial diet supported a viability of 81% of the eggs, while only 40% developed on the natural diet. Life-table data showed the same pattern: the net reproductive rate (Ro) of C. vestigialis reared on the artificial diet was 401.70, and on the natural diet was 151.22. The artificial diet is adequate for mass rearing of C. vestigialis, to support biological control programs using the baculovirus.